2019
DOI: 10.1111/ecog.04544
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal scaling of biodiversity in acoustic tropical bird communities

Abstract: Automated analysis of acoustic communities is a rapidly emerging approach for the characterization and monitoring of biodiversity. To evaluate its utility, we should verify that such 'bioacoustics' can accurately detect ecological signal in spatiotemporal acoustic data. Targeting the 'Biological Dynamics of Forest Fragments Project' sites in Brazil, we ask: What is the relative contribution of the spatial, temporal and habitat dimension to variation in bird acoustic communities in a previously fragmented tropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 76 publications
(192 reference statements)
2
20
0
Order By: Relevance
“…Independent of the ANH, consistent acoustic fingerprints among replicate sites and daily surveys suggest that network-based analyses of soundscapes may help differentiate among transient typologies of forest succession. These results corroborate previous reports based on acoustic studies of birds that soundscapes function as memory banks of Amazon forest modification (33), but this study goes further to demonstrate that soundscapes may be most valuable when collected as 24-hr records that capture more acoustically active taxa and their network-level interactions.…”
Section: Discussionsupporting
confidence: 91%
“…Independent of the ANH, consistent acoustic fingerprints among replicate sites and daily surveys suggest that network-based analyses of soundscapes may help differentiate among transient typologies of forest succession. These results corroborate previous reports based on acoustic studies of birds that soundscapes function as memory banks of Amazon forest modification (33), but this study goes further to demonstrate that soundscapes may be most valuable when collected as 24-hr records that capture more acoustically active taxa and their network-level interactions.…”
Section: Discussionsupporting
confidence: 91%
“…NMS ordinations clearly indicated a separation between samples from the two plots, with annual samples from the same plot more similar to each other than to samples from the other plot, even after eliminating species recorded only once. Similarly, De Camargo, Roslin & Ovaskainen (2019) found that composition at a given point differed less between years than composition at different sites in the same year. The ordination also illustrated that composition changed across years in a similar way between plots—that is, direction of change in composition was similar even when the compositions differed between plots.…”
Section: Discussionmentioning
confidence: 87%
“…Acoustic monitors have proven to be useful for sampling bird species in a variety of habitats, including both temperate ( Celis-Murillo, Deppe & Allen, 2009 ; Depraetere et al, 2011 ; Cook & Hartley, 2018 ) and tropical ( Bueno et al, 2012 ; De Camargo, Roslin & Ovaskainen, 2019 ; Stevens et al, 2019 ) forests. They have been used to provide descriptions of bird species richness, community composition, and change in such communities over space and time ( Towsey et al, 2014 ; De Camargo, Roslin & Ovaskainen, 2019 ; Stevens et al, 2019 ). Recordings from acoustic monitors also have been used to develop acoustic indices that provide information on diversity, without identification of individual species ( Depraetere et al, 2011 ; Towsey et al, 2014 ; Aide et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…NMS ordinations clearly indicated a separation between samples from the two plots, with annual samples from the same plot more similar to each other than to samples from the other plot, even after eliminating species recorded only once. Similarly, De Camargo, Roslin & Ovaskainen (2019) found that composition at a given point differed less between years than composition at different sites in the same year. The ordination also illustrated that composition changed across years in a similar way between plots-that is, direction of change in composition was similar even when the compositions differed between plots.…”
Section: Community Compositionmentioning
confidence: 79%
“…Full-size  DOI: 10.7717/peerj.10565/ fig-6 DISCUSSION Acoustic monitors have proven to be useful for sampling bird species in a variety of habitats, including both temperate (Celis-Murillo, Deppe & Allen, 2009;Depraetere et al, 2011;Cook & Hartley, 2018) and tropical (Bueno et al, 2012;De Camargo, Roslin & Ovaskainen, 2019;Stevens et al, 2019) forests. They have been used to provide descriptions of bird species richness, community composition, and change in such communities over space and time (Towsey et al, 2014;De Camargo, Roslin & Ovaskainen, 2019;Stevens et al, 2019). Recordings from acoustic monitors also have been used to develop acoustic indices that provide information on diversity, without identification of individual species (Depraetere et al, 2011;Towsey et al, 2014;Aide et al, 2017).…”
Section: Community Compositionmentioning
confidence: 99%